Pengaruh Suhu Pengeringan terhadap Karakteristik Teh Buah Mahkota Dewa (Phaleria macrocarpa) sebagai Minuman Fungsional: The Effect of Drying Temperature on the Properties Of Gods Crown (Phaleria macrocarpa) Fruit Tea as a Functional Beverage - Hartisyah, Nurul; Nazaruddin, Nazaruddin; Utama, Qabul Dinanta (Jurnal Teknologi dan Mutu Pangan, 2024)
The God's Crown (Phaleria macrocarpa) fruit contains active compounds such as alkaloids, saponins, flavonoids, polyphenols, and tannins, which are beneficial for health, making it a potential functional beverage. This study aims to evaluate the effect of drying temperature on the physical, chemical, and organoleptic properties of Mahkota Dewa fruit tea. A Completely Randomized Design (CRD) method was used, consisting of five drying temperature treatments: P0 (30 °C), P1 (40 °C), P2 (50 oC), P3 (60 oC), and P4 (70 oC). Data analysis was performed using analysis of variance (ANOVA) at a 5% significance level, followed by the Honest Significant Difference (HSD) test. The results showed that drying temperature significantly affected antioxidant activity, moisture content, ash content, pH, hue value, aroma (score), taste (hedonic and score), and color (score). However, there were no significant differences in the hedonic tests for aroma and color. The best treatment was found at 60 oC (P3) with a moisture content of 7.81%, ash content of 4.22%, pH of 5.606, and a hue value of 82.92, resulting in a yellowish-red color. Organoleptic properties indicated a tea with a distinctive aroma and a bitter taste. The highest antioxidant activity was recorded at 30 oC (P0) with 81.70%. This research contributes to identifying the optimal drying temperature that can improve the physical, chemical, and organoleptic quality of Dewa Crown fruit tea.